Advanced Stage of Medication‐Related Osteonecrosis of the Jaw Associated With Oral Bisphosphonates: Report of Three Cases. Issue 2 (1st May 2017) - Ojha, Junu; Cohen, Donald M.; Choi, Hyden; Schumer, Joseph; Gupta, Anish; Dang, Nathen
Abstract : Introduction: Bisphosphonates (BPs) are prescribed for treating diseases exhibiting high bone turnover rates. Medication‐related osteonecrosis of the jaw (MRONJ) is a major adverse effect of BPs. Cases of MRONJ associated with oral BPs for treatment of osteoporosis are much less common compared with intravenous BPs. Most reports of oral BP–associated MRONJ are either stage 1 or stage 2 as classified by the 2014 American Academy of Oral and Maxillofacial Surgeons position paper (Ruggiero et al., J Oral Maxillofac Surg 2014;72:1938‐1956). There are ≈24 reported cases of oral BP–induced stage 3 MRONJ presenting as an area of exposed necrotic bone with pain and infection along with a pathologic fracture, an extraoral fistula, oroantral communication, or osteolysis extending to the inferior border of the mandible or sinus floor. Case Series: Three cases of stage 3 MRONJ associated with oral BPs are presented. All three patients had a long history of use of alendronate for over 10 years. Diagnosis of stage 3 MRONJ was made based on clinical, radiographic, and histopathologic findings. Patients were managed with a course of antibiotics and removal of the necrotic bone. Conclusions: Development of stage 3 MRONJ associated with oral BPs is relatively rare. However, there is an increased risk of advanced MRONJ associated with oral BPs in the presence of longer duration of therapy, dentoalveolar surgery, denture trauma, inflammatory oral diseases, and presence of comorbid factors. Therefore, it is recommended that clinicians educate patients about the advanced adverse effects of oral BPs.